2014
DOI: 10.1016/j.urology.2014.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Adult Prostate Sarcoma: The Memorial Sloan Kettering Experience

Abstract: Objectives To present our institutional experience with adult prostate sarcoma over 30 years. Methods We reviewed 38 cases of adult prostate sarcoma diagnosed and treated at our institution between 1982 and 2012. Univariate Cox proportional hazards regression was used to determine if there was an association between specific disease characteristics (tumor size, histology, AJCC stage, and metastasis at diagnosis) and cancer-specific survival (CSS). Results A total of 38 patients were included, with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Because of their different natural history, sarcomas arising from different parts of the urogenital system should be managed accordingly. In a population of 38 PS patients, Musser et al confirmed that the presence of metastatic disease is a poor prognostic factor for CSS (HR: 5.91, 95%CI: 2.31‐15.11, P = 0.0002). These authors also showed that rhabdomyosarcoma patients have the poorest CSS compared to leiomyosarcomas patients (HR: 3.00, range: 1.13‐7.92, P = 0.027).…”
Section: Discussionmentioning
confidence: 95%
“…Because of their different natural history, sarcomas arising from different parts of the urogenital system should be managed accordingly. In a population of 38 PS patients, Musser et al confirmed that the presence of metastatic disease is a poor prognostic factor for CSS (HR: 5.91, 95%CI: 2.31‐15.11, P = 0.0002). These authors also showed that rhabdomyosarcoma patients have the poorest CSS compared to leiomyosarcomas patients (HR: 3.00, range: 1.13‐7.92, P = 0.027).…”
Section: Discussionmentioning
confidence: 95%
“…Sarcomas of the prostate account for 0.7% of all malignant prostatic tumors [4]. Forty percent of MPNSTs are sporadic and the incidence in the general population is 0.001% [1, 3].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining sarcomas described include prostatic stromal sarcoma, synovial sarcoma, malignant peripheral nerve sheath tumor, osteosarcoma, Ewing sarcoma/primitive neuroectodermal tumor, angiosarcoma, undifferentiated sarcoma, and mixed sarcomas. 13,[19][20][21] CURRENT TREATMENT The rare incidence of intraprostatic synovial sarcoma presents a challenge to the establishment of best practices. Each case presented in the literature thus far has been treated with a combination of surgical resection, chemotherapy, and/or radiation therapy.…”
Section: Differential Diagnosismentioning
confidence: 99%